Hubungan D-dimer dan Trombosit pada Pasien COVID-19 - Apriani; Fenny Ong Lian Hwa (Journal of Health (JoH), 2022)
Examination of D-dimer and platelets in COVID-19 patients is very important, especially to assess the severity of the disease and the risk of not surviving in these patients. The D-dimer value is used to assess the occurrence of the coagulation process in COVID-19 patients, while the platelet count is calculated to see the risk of thrombocytopenia. This study aims to analyze the relationship between D-dimer levels and platelet levels in COVID-19 patients. The D-dimer sample was analyzed using the Cobas Analyzer series, and the platelet sample was analyzed using the sysmex KX-21 hematolyzer. This research is analytic retrospective with cross sectional approach. The data source comes from the results of the examination of COVID-19 patients at the hospital Siloam Lippo Village. The research sample obtained as many as 94 samples taken by purposive sampling technique. The test results using the Spearman's rho correlation test with a= 0.05 showed no significant relationship between D-dimer levels and platelet count (r = -0.72, P = 0.488). Elevated D-dimer levels are not directly proportional to the condition of thrombocytopenia which is an indication of severity in COVID-19 patients. Further research is suggested to be able to analyze the parameters of other examination results in COVID-19 patients that lead to the condition of patients who do not survive such as inflammatory marker parameters. Keywords: COVID-19, D-dimer, Platelets